Small-particle-size allophane-amidoximation polyacrylonitrile composite material for extracting uranium from seawater and preparation method of small-particle-size allophane-amidoximation polyacrylonitrile composite material
By preparing a small-particle-size hydramid-aluminum-pyramide polypropylene compound material, the nano-structure and surface group characteristics are used to solve the high cost and energy consumption of uranium ion in the seawater. Achieve efficient and economical uranium -ion adsorption effects.
Patent Information
- Application Number
- CN202411812831.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-10
- Publication Date
- 2025-01-21
- Estimated Expiration
- 2044-12-10
AI Technical Summary
The prior art methods for efficiently enriching uranyl ions in seawater are costly and have high energy consumption, and the adsorption effect of materials is limited, making it difficult to meet the sustainable development needs of nuclear energy.
By convergence of hydrocytic aluminum and acrylics on the root ion of sulfate, and prepare a small-particle-size hydramidi-aluminum-pyrine-pyrium composite material through the reaction of pyrine, the uniqueness The nano structure and surface group characteristics improve the adsorption capacity of uranium ions.
It achieves efficient adsorption of uranyl ions, with an adsorption capacity of 320-480 mg/g, and maintains an adsorption capacity of no less than 85% after multiple cycles, reducing production complexity and raw material costs.
Smart Images

Figure CN119327435A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a uranium adsorption material and a preparation method thereof, and belongs to the fields of adsorption materials, water treatment and nuclear chemical industry, and in particular to a small-particle-size allophane-amidoxime-modified polyacrylonitrile composite material and a preparation method thereof. Technical Background
[0002] Uranium is a basic resource for the nuclear industry, and its reserves and mining technology directly affect the country's national defense security and energy security. As an important clean energy source, nuclear power generation will have 55 nuclear power units in operation by the end of 2023, with annual nuclear power generation reaching 440,000 GWh, accounting for nearly 5% of the country's cumulative power generation. The continuous operation of nuclear energy requires a stable supply of uranium resources. However, my country's proven uranium reserves are only 2.8 million tons. In the face of such high consumption, it is urgent to increase investment in uranium exploration and mining to ensure the sustainable development of nuclear energy.
[0003] Since uranium resources in the earth's crust are relatively limited, about 99.9% of the world's uranium resources exist in the form of uranyl ions in seawater. Therefore, how to obtain uranium resources from seawater has become a strategic technology to ensure the sustainable development of nuclear energy. Thanks to the potential contribution of seawater uranium extraction technology to energy security, it was rated as one of the seven separation technologies that changed the world by the journal Nature in 2016. However, the uranium concentration in seawater is extremely low (about 3.2 μg / L), and it usually takes hundreds of tons of uranium fuel to start a nuclear power plant. Therefore, how to enrich uranyl ions in seawater at low cost and high efficiency has become a key issue for the widespread promotion of nuclear energy.
[0004] Since Davies et al. first published their research on uranium extraction from seawater in 1964, a variety of methods for extracting uranium have been developed, including adsorption, solvent extraction, chemical precipitation, biological treatment, ion exchange, and superconducting magnetic separation. Among them, the adsorption method has become the focus of research due to its low cost, low energy consumption, and mature process. Polymer materials containing amidoxime groups have high adsorption capacity and selectivity for uranyl ions and are popular candidates for adsorption materials for uranium extraction from seawater.
[0005] Acrylonitrile and its polymers contain a large number of nitrile functional groups, which can be converted into amidoxime groups through simple chemical reactions. They are widely used as precursors for the preparation of uranyl ion adsorption materials. However, due to the limited accessibility of amidoxime groups in large-particle polymers, the actual adsorption capacity of polyacrylonitrile-based adsorption materials is far lower than the theoretical capacity. The adsorption effect of uranium in related reports only reached 13.1 mg / g (Polyamidoxime (PAO) granules for solar-enhanced uranium extraction from seawater Environmental Science Advances 20243.4). Therefore, it is an important direction to improve the adsorption capacity of these materials by optimizing the material structure and controlling the particle size of the polymer to increase the accessibility of the adsorption group.
[0006] Chinese invention patent CN201710665074.0 discloses a nanofiber material for extracting uranium from seawater and a preparation method thereof. Nano-scale amidoxime-modified polyacrylonitrile fibers are prepared by electrospinning for uranyl ion adsorption. This method solves the problem of uranyl ion migration from seawater to polyacrylonitrile fibers to a certain extent by preparing nanofibers, and obtains a relatively stable adsorption material. However, due to the steric hindrance effect when uranyl ions diffuse inside the material, the adsorption effect of a single polyacrylonitrile material on uranyl ions is limited. Researchers have tried to compound two or more materials to overcome this problem. Chinese invention patent CN202210423039.9 Nanoporous structure of seawater uranium extraction adsorption material and pore size control preparation method The amidoxime-modified bamboo strip composite material is prepared by cross-linking reaction and hydrolysis reaction with bamboo strips as the matrix. This material has a nanoporous structure, which significantly promotes the diffusion effect of uranyl ions. However, the pretreatment process of the bamboo strip matrix material is complicated, and the adsorption effect per unit mass is low, which is not conducive to the industrial application of uranium extraction from seawater.
[0007] And Chinese patent CN201910269879.2 discloses a uranium adsorption material and preparation method of a mesoporous silica particle loaded amidoxime polymer, which uses mesoporous silica particles as a matrix, loads finished polyacrylonitrile and converts its amidoxime to prepare a uranium adsorption material of mesoporous silica particles loaded with amidoxime polymer. The adsorbent obtained by this process has a certain adsorption effect on uranyl ions. However, the process is complicated, and the molecular weight of the amidoxime polymer in the prepared mesoporous silica particle loaded amidoxime polymer uranium adsorption material depends entirely on the molecular weight of polyacrylonitrile in the raw material, and this limitation is also not conducive to the industrial application of seawater uranium extraction. Therefore, selecting a composite phase with good synergy with polyacrylonitrile and a composite adsorbent material that can be obtained by a simple preparation process is a research hotspot for preparing industrial seawater uranium extraction adsorption materials.
[0008] Allophane is a nano-scale hydrated aluminum silicate clay mineral widely found in volcanic ash, and its structure has a unique short-range order. Its outer layer is aluminum oxide octahedron, and its inner layer is silicon oxide tetrahedron. The two form a 3.5-5.0 nm nano hollow sphere structure, and there are a large number of active aluminum hydroxyls on the outer surface. This structure gives allophane a large specific surface area and excellent reactivity, and it has great application potential in the field of adsorption.
[0009] At present, there are no reports on the application of allophane in the adsorption of uranyl ions. This is due to the complexity of the inorganic-organic composite process of allophane and the limitations of existing technologies in the study of nano properties. Therefore, developing a simple and efficient composite method and constructing a synergistic small-particle allophane-amidoxime polyacrylonitrile composite material is of great significance for the preparation of efficient adsorption composite materials that can be used in industrial seawater uranium extraction projects. Summary of the invention
[0010] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a small-particle allophane-amidoxime-treated polyacrylonitrile composite material for extracting uranium from seawater, a preparation method thereof and corresponding applications.
[0011] One of the purposes of the present invention is to provide a small-particle allophane-amidoxime-treated polyacrylonitrile composite material for extracting uranium from seawater.
[0012] The second object of the present invention is to provide a method for preparing the above-mentioned small-particle allophane-amidoxime-treated polyacrylonitrile composite material for extracting uranium from seawater.
[0013] The third object of the present invention is to provide the application of the above-mentioned small-particle allophane-amidoxime-treated polyacrylonitrile composite material for extracting uranium from seawater.
[0014] To achieve the above purpose, the technical solution adopted by the present invention is as follows: In a first aspect, the present invention provides a small-particle allophane-amidoxime-treated polyacrylonitrile composite material for extracting uranium from seawater. The composite material is obtained by polymerizing allophane and acrylonitrile under the initiation of persulfate ions and undergoing an amidoxime reaction, wherein the allophane is nanoscale.
[0015] Preferably, the particle size of the allophane is 3.5-5.0 nm, and the allophane structure is a nano hollow sphere with defect holes of 0.3-0.5 nm. Preferably, the allophane comes from an allophane suspension, and the allophane suspension is an undried allophane suspension.
[0016] Preferably, the polyacrylonitrile is prepared by polymerizing acrylonitrile monomer, and is compounded with allophane during the polymerization process, and finally subjected to amidoximation reaction using a hydroxylamine hydrochloride solution.
[0017] Preferably, the average particle size of the composite material is 26-35 nm, and the median cluster size of the composite material is 480-560 nm.
[0018] Preferably, the molar ratio of the nitrile functional group of the polyacrylonitrile to hydroxylamine hydrochloride is 1:0.1-1:10. Preferably, the relative molecular weight of the polyacrylonitrile after polymerization is 70,000-80,000.
[0019] Preferably, the mass ratio of the allophane to acrylonitrile is 2:1-20:1.
[0020] Preferably, the hydroxylamine hydrochloride solution is prepared by dissolving hydroxylamine hydrochloride and an alkaline compound in methanol or water, wherein the alkaline compound is one or more of sodium hydroxide, sodium carbonate, sodium bicarbonate, and potassium hydroxide; the molar ratio of the added alkaline compound to hydroxylamine hydrochloride is 1:0.5-1:5; the content of hydroxylamine hydrochloride in the hydroxylamine hydrochloride solution is 30-60 g / L, preferably 40-55 g / L.
[0021] The allophane suspension is prepared by the following method: A certain concentration of sodium orthosilicate solution (Na4SiO4) is mixed with a certain concentration of aluminum chloride hexahydrate (AlCl3-6H2O) solution; the mixture is continuously stirred for 0.5-2 hours under the condition that the silicon / aluminum molar ratio is controlled to be 0.6-0.9, preferably 0.75-0.8, the obtained precursor is centrifuged at a speed of 3000-8000 r / min for 10-30 minutes, the obtained white precipitate is hydrothermally treated at 100°C for 2-48 hours, and the obtained product is dialyzed with ultrapure water until the pH value is close to neutral to obtain a hydroalophane suspension.
[0022] Preferably, the concentration of the sodium silicate solution is 0.05-0.3 mol / L, and the concentration of the aluminum chloride hexahydrate is adaptively configured according to the silicon / aluminum molar ratio based on the concentration of the sodium silicate solution.
[0023] In a second aspect, the present invention provides a method for preparing a small-particle allophane-amidoxime-treated polyacrylonitrile composite material for extracting uranium from seawater, comprising the following steps: a) preparing an allophane suspension, adding a persulfate ion solution, stirring and reacting to obtain a reaction solution; b) adding acrylonitrile monomer to the reaction solution obtained in step a) and heating and aging the mixture to form a polyacrylonitrile / alophane composite material; c) subjecting the composite material obtained in step b) to amidoximation reaction to obtain a small-particle-size allophane-amidoximated polyacrylonitrile composite material.
[0024] Preferably, the persulfate ion is from any one or more of potassium persulfate, ammonium persulfate or sodium persulfate, and the concentration of the persulfate ion is 1-10 g / L.
[0025] Preferably, the acrylonitrile in step b) is treated by distillation or other methods to remove the anticoagulant.
[0026] Preferably, the amidoximation reaction occurs in a liquid medium, and the liquid medium is water or any one of dimethylformamide, dimethyl sulfoxide, cyclopentane, and ethyl nitrate.
[0027] Preferably, the concentration of the allophane suspension is 10-200 g / L, and the allophane is an artificially synthesized suspension and has not been dried.
[0028] The allophane suspension is prepared by the following method: A certain concentration of sodium orthosilicate solution (Na4SiO4) is mixed with a certain concentration of aluminum chloride hexahydrate (AlCl3-6H2O) solution; the mixture is continuously stirred for 0.5-2 hours under the condition that the silicon / aluminum molar ratio is controlled to be 0.6-0.9, preferably 0.75-0.8, the obtained precursor is centrifuged at a speed of 3000-8000 r / min for 10-30 minutes, the obtained white precipitate is hydrothermally treated at 100°C for 2-48 hours, and the obtained product is dialyzed with ultrapure water until the pH value is close to neutral to obtain a hydroalophane suspension.
[0029] Preferably, the concentration of the sodium silicate solution is 0.05-0.3 mol / L, and the concentration of the aluminum chloride hexahydrate is adaptively configured according to the silicon / aluminum molar ratio based on the concentration of the sodium silicate solution.
[0030] Preferably, the molar ratio of the nitrile functional group of the polyacrylonitrile to hydroxylamine hydrochloride is 1:0.1-1:10. Preferably, the relative molecular weight of the polyacrylonitrile after polymerization is 70,000-80,000.
[0031] Preferably, the mass ratio of the allophane to the polyacrylonitrile material is 2:1-20:1.
[0032] Preferably, the hydroxylamine hydrochloride solution is prepared by dissolving hydroxylamine hydrochloride and an alkaline compound in methanol or water, wherein the alkaline compound is one or more of sodium hydroxide, sodium carbonate, sodium bicarbonate, and potassium hydroxide; the molar ratio of the added alkaline compound to hydroxylamine hydrochloride is 1:0.5-1:5; the content of hydroxylamine hydrochloride in the hydroxylamine hydrochloride solution is 30-60 g / L, preferably 40-55 g / L.
[0033] Preferably, the reaction time of step a) is 0.1-3 h.
[0034] Preferably, the heating and aging time in b) is 1-4 h, preferably 2-3 h, and the reaction time of adding acrylonitrile monomer is 0.1-3 h, preferably 0.5-0.8 h.
[0035] Preferably, the amidoximation conversion time in step c) is 15-30 h, preferably 18-25 h, more preferably 20 h.
[0036] Preferably, CH (2933, 2856 cm -1 )、CN(1438 cm -1 ) and C=N(1391 cm -1 ) and other characteristic chemical bonds of amidoximated polyacrylonitrile, as well as Si-O-(Al) (982 cm -1 )、Si-O-Al(680 cm -1 ) and other characteristic chemical bonds of hydroalophane.
[0037] In a third aspect, the present invention provides an application of a small-particle allophane-amidoxime-treated polyacrylonitrile composite material for extracting uranium from seawater, which adsorbs uranyl ions at room temperature, wherein the uranyl ion concentration is 8-20 ppm.
[0038] Preferably, the adsorption capacity of the small-particle allophane-amidoxime polyacrylonitrile composite material for uranyl ions at room temperature for 2-5 h is 320-480 mg / g when the uranyl ion concentration is 8-20 ppm.
[0039] Preferably, the small-particle allophane-amidoxime-polyacrylonitrile composite material still has an adsorption capacity for uranyl ions of not less than 85% after 5-10 regeneration cycles.
[0040] Compared with the prior art, the present invention has the following beneficial effects: The present invention creatively utilizes the nanostructure and surface group characteristics of allophane, and through a composite reaction with acrylonitrile, constructs a preparation method and application of a small-particle allophane-amidoxime polyacrylonitrile composite material: 1. Allophane-amidoxime polyacrylonitrile composite materials with abundant adsorption sites for uranyl ions are constructed by utilizing the unique nanosphere structure and surface hydroxyl properties of allophane. The surface of allophane has a large number of active hydroxyl sites, which can serve as the starting point and end point of acrylonitrile polymerization. Its unique nanosphere structure enables it to be evenly dispersed in the reaction solution, effectively interrupting the overlong main chain formed during the polymerization of acrylonitrile, and avoiding the folding and distortion of single-phase polyacrylonitrile due to the overlong main chain. Therefore, the amidoxime groups of the allophane-amidoxime polyacrylonitrile composite materials are fully exposed, significantly inhibiting the steric hindrance effect inside the material during the adsorption process, so that the composite materials can efficiently capture a large number of uranyl ions, thus having excellent adsorption performance.
[0041] 2. The synergistic effect of allophane and polyacrylonitrile gives the composite material excellent suspension and structural stability. The average particle size of the allophane-polyacrylonitrile composite material of the present invention is only about 30 nm after the amidoximation transformation, and the cluster particle size maintained in the solution is small (about 542 nm), so that it has good suspension in the solution and can be suspended in the aqueous solution for a long time, effectively avoiding the sedimentation and failure of the adsorbent material during the adsorption of uranyl ions, so that the material maintains excellent adsorption capacity for uranyl ions in static solution. This is conducive to the application scenario of the material in the unpowered adsorption bed in the process of uranium extraction from seawater, which helps to reduce the energy consumption and maintenance cost of the adsorption equipment. On the other hand, the separation of amidoxime groups and uranyl ions needs to be carried out in an alkaline environment, which will cause irreversible changes in the structure of the adsorbent material, such as main chain breakage. By grafting short-chain polyacrylonitrile on the surface of allophane, a short-chain amidoxime polyacrylonitrile adsorption system with allophane as the core is constructed. The short-chain polymer can maintain good structural stability under alkaline conditions, significantly reducing the failure caused by main chain breakage during the regeneration process. Therefore, the material can maintain efficient adsorption performance over multiple cycles and is suitable for continuous application scenarios such as uranium extraction from seawater.
[0042] 3. Inorganic-organic polymerization is achieved through a "one-step" in-situ copolymerization reaction, which has the advantage of a simple preparation method. The hydroxyl groups on the surface of allophane are treated with persulfate ions to promote the polymerization between allophane and acrylonitrile, avoiding the need to use silane and other modifiers to perform additional organic modification on inorganic materials in the preparation process of traditional inorganic-organic composite materials. The hydrolysis product of persulfate ions can not only promote the conversion of hydroxyl groups on the surface of allophane to alkoxy free radicals, but also open the double bond of acrylonitrile in subsequent reactions, initiating polymerization between the two under milder conditions. Therefore, this "one-step" process reduces the complexity of production and the cost of raw materials, creating favorable conditions for the actual industrial application of uranyl ion adsorption materials. BRIEF DESCRIPTION OF THE DRAWINGS
[0043] Figure 1 This is an X-ray diffraction (XRD) diagram of the small-particle allophane-amidoxime-treated polyacrylonitrile composite material prepared in Example 1.
[0044] Figure 2 This is a Fourier transform infrared spectrum (FT-IR) diagram of the small-particle allophane-amidoxime-treated polyacrylonitrile composite material prepared in Example 1.
[0045] Figure 3 This is a transmission electron microscope (TEM) image of the small-particle allophane-amidoxime-treated polyacrylonitrile composite material prepared in Example 2.
[0046] Figure 4 This is a laser particle size (LPS) graph of the small-particle allophane-amidoxime-treated polyacrylonitrile composite material prepared in Example 2 in aqueous solution. DETAILED DESCRIPTION
[0047] The present invention is described in detail below in conjunction with examples, but the implementation manner and protection scope of the present invention are not limited to the following examples. Example 1
[0048] 1) Take 0.5 mL of 100 g / L allophane suspension, add 9 mL of 5.56 g / L potassium persulfate solution and stir for 0.5 h to obtain a reaction solution.
[0049] 2) Add 0.5 mL of acrylonitrile to the reaction solution obtained in step 1), stir for 0.5 h, and then heat to 70° C. and age for 2 h to obtain a polyacrylonitrile / alophane composite material.
[0050] 3) Add 5.3 g of hydroxylamine hydrochloride to 100 mL of water, wait for complete dissolution, add a mixed powder of 3.6 g of sodium carbonate and 0.9 g of sodium hydroxide, stir, add 0.5 g of the polyacrylonitrile / alophane composite material obtained in step 2), heat to 70 ° C and maintain for 20 h to complete the amidoximation transformation of the polyacrylonitrile in the composite material, and obtain the small-particle allophane-amidoximated polyacrylonitrile composite material of this embodiment.
[0051] Figure 1 3 is the XRD spectrum of this example. The analysis result shows that the diffraction peaks of amidoximated polyacrylonitrile and allophane exist at the same time, indicating that amidoximated polyacrylonitrile and allophane exist at the same time in the composite material.
[0052] Figure 2 The FT-IR spectrum of this example shows that CH (2933, 2856 cm -1 )、CN(1438 cm -1 ) and C=N(1391 cm -1 ) and other characteristic chemical bonds of amidoximated polyacrylonitrile, as well as Si-O-(Al) (982 cm -1 )、Si-O-Al(680 cm -1 ) and other characteristic chemical bonds of allophane, further proving the coexistence of amidoxime-modified polyacrylonitrile and allophane in the composite material.
[0053] After adsorbing in 100 mL of uranyl solution containing 8 ppm of uranium for 5 h, the uranium adsorption capacity of the small-particle allophane-amidoxime-treated polyacrylonitrile composite material obtained in Example 1 reached 413.3 mg / g. Example 2
[0054] 1) Take 0.5 mL of 30 g / L allophane suspension, add 9 mL of 6 g / L potassium persulfate solution and stir for 0.5 h to obtain a reaction solution.
[0055] 2) Add 0.5 mL of acrylonitrile to the reaction solution obtained in step 1), stir for 0.5 h, and then heat to 70° C. and age for 2 h to obtain a polyacrylonitrile / alophane composite material.
[0056] 3) Add 2.5 g of hydroxylamine hydrochloride to 30 mL of dimethylformamide, wait for complete dissolution, add a mixed powder of 2.0 g of sodium carbonate and 0.5 g of sodium hydroxide, stir, add 0.1 g of the polyacrylonitrile / alophane composite material obtained in step 2), heat to 70°C and keep for 20 h, then add 2.0 g of sodium carbonate and 0.5 g of sodium hydroxide, and continue to keep for 20 h to complete the amidoximation transformation of polyacrylonitrile in the composite material, and obtain the small-particle allophane-amidoximated polyacrylonitrile composite material of this embodiment.
[0057] Figure 3 TEM image of this example shows that the particle size of the allophane-amidoxime-polyacrylonitrile in this example is about 30 nm, and clusters of about 500 nm are formed after drying.
[0058] Figure 4 : is the laser particle size diagram measured in water in this embodiment. According to the cumulative particle size distribution curve, it can be seen that the median cluster particle size in this embodiment is 541.6 nm, indicating that the composite material synthesized in this embodiment still has a smaller cluster particle size in water, proving that the addition of hydroalophane inhibits the agglomeration of amidoxime-modified polyacrylonitrile in water, and is more conducive to inhibiting the steric hindrance effect existing when uranyl ions diffuse therein.
[0059] After adsorbing in a uranyl solution containing uranium at a concentration of 8 ppm for 5 h, the uranium adsorption capacity of the small-particle allophane-amidoxime-treated polyacrylonitrile composite material obtained in Example 2 reached 459.1 mg / g. Example 3
[0060] 1) Take 1.7 mL of 58.3 g / L allophane suspension, add 18 mL of 8 g / L ammonium persulfate solution and stir for 0.2 h to obtain a reaction solution.
[0061] 2) Add 1 mL of acrylonitrile to the reaction solution obtained in step 1), stir for 0.5 h, and then heat to 75° C. and age for 2 h to obtain a polyacrylonitrile / alophane composite material.
[0062] 3) Add 3 g of hydroxylamine hydrochloride to 30 mL of dimethylformamide, wait for complete dissolution, add a mixed powder of 2 g of sodium carbonate and 0.5 g of sodium hydroxide, stir, add 0.2 g of the polyacrylonitrile / alophane composite material obtained in step 2), heat to 75°C and maintain for 5 h to complete the amidoximation transformation of the polyacrylonitrile in the composite material, and obtain the small-particle allophane-amidoximated polyacrylonitrile composite material of Example 3.
[0063] The uranium adsorption capacity of the small-particle allophane-amidoxime-treated polyacrylonitrile composite material obtained in this example reached 327.6 mg / g after adsorption in 100 mL uranyl solution with a uranium concentration of 8 ppm for 5 h. After desorption and regeneration in hot sodium hydroxide solution for 5 times, it still retained 85.3% (279.5 mg / g) of the efficient adsorption capacity. Comparative Example 1
[0064] 1) Take 2 mL of 35 g / L mesoporous silica particle suspension, add 20 mL of 8 g / L ammonium persulfate solution and stir for 0.2 h to obtain a reaction solution. The mesoporous silica particles are commercial mesoporous silica with an average particle size of 200 nm and a pore size of 2 nm, which are from MacLean reagent M758933.
[0065] 2) Add 1 mL of acrylonitrile to the reaction solution obtained in step 1) and stir for 0.5 h, then heat to 75° C. and age for 2 h to obtain a polyacrylonitrile / mesoporous silica particle composite material.
[0066] 3) Add 3 g of hydroxylamine hydrochloride to 30 mL of dimethylformamide, wait for it to be completely dissolved, add a mixed powder of 2 g of sodium carbonate and 0.5 g of sodium hydroxide, stir, add 0.2 g of the polyacrylonitrile / mesoporous silica particle composite material obtained in step 2), heat to 75°C and maintain for 5 h to complete the amidoximation transformation of the polyacrylonitrile in the composite material, and obtain the mesoporous silica particle-amidoximated polyacrylonitrile composite material of this comparative example.
[0067] The adsorption capacity of the mesoporous silica gel particle-amidoxime polyacrylonitrile composite material obtained in this comparative example reached 85.6 mg / g after adsorption in 100 mL uranyl solution with a uranium concentration of 8 ppm for 5 h. Comparative Example 2
[0068] 1) Take 50 mg of allophane and ultrasonically disperse it in 0.5 mL of water, add 9 mL of 5.56 g / L potassium persulfate solution to the allophane dispersion and stir for 0.5 h to obtain a reaction solution. The allophane is the allophane powder obtained by drying the allophane suspension in Example 1-3.
[0069] 2) Add 0.5 mL of acrylonitrile to the reaction solution obtained in step 1), stir for 0.5 h, and then heat to 70° C. and age for 2 h to obtain a polyacrylonitrile / alophane composite material.
[0070] 3) Add 5.3 g of hydroxylamine hydrochloride to 100 mL of water, wait for it to be completely dissolved, add a mixed powder of 3.6 g of sodium carbonate and 0.9 g of sodium hydroxide, stir, add 0.5 g of the polyacrylonitrile / alophane composite material obtained in step 2), heat to 70°C and maintain for 20 h to complete the amidoximation transformation of the polyacrylonitrile in the composite material, and obtain the allophane-amidoximated polyacrylonitrile composite material of this comparative example.
[0071] The adsorption capacity of the allophane-amidoxime-polyacrylonitrile composite material obtained in this comparative example was 102 mg / g after adsorption in 100 mL of uranyl solution containing uranium at a concentration of 8 ppm for 5 h. Comparative Example 3
[0072] 1) Take 25 mg of allophane and ultrasonically disperse it in 0.5 mL of water, add 9 mL of 5.56 g / L potassium persulfate solution to the allophane dispersion and stir for 0.5 h to obtain a reaction solution. The allophane is the allophane powder obtained by drying the allophane suspension in Example 1-3.
[0073] 2) Add 0.5 mL of acrylonitrile to the reaction solution obtained in step 1), stir for 0.5 h, and then heat to 70° C. and age for 2 h to obtain a polyacrylonitrile / alophane composite material.
[0074] 3) Add 5.3 g of hydroxylamine hydrochloride to 100 mL of water, wait for it to be completely dissolved, add a mixed powder of 3.6 g of sodium carbonate and 0.9 g of sodium hydroxide, stir, add 0.5 g of the polyacrylonitrile / alophane composite material obtained in step 2), heat to 70°C and maintain for 20 h to complete the amidoximation transformation of the polyacrylonitrile in the composite material, and obtain the allophane-amidoximated polyacrylonitrile composite material of this comparative example.
[0075] The adsorption capacity of the allophane-amidoxime-polyacrylonitrile composite material obtained in this comparative example was 35 mg / g after adsorption in 100 mL of uranyl solution containing uranium at a concentration of 8 ppm for 5 h. Comparative Example 4
[0076] 1) Take 50 mg of sodium montmorillonite and disperse it in 0.5 mL of water by ultrasonication, add 9 mL of 5.56 g / L potassium persulfate solution to the sodium montmorillonite dispersion and stir for 0.5 h to obtain a reaction solution. The sodium montmorillonite is a nano-scale powder.
[0077] 2) Add 0.5 mL of acrylonitrile to the reaction solution obtained in step 1), stir for 0.5 h, and then heat to 70° C. and age for 2 h to obtain a polyacrylonitrile / sodium-montmorillonite composite material.
[0078] 3) Add 5.3 g of hydroxylamine hydrochloride to 100 mL of water, wait for it to be completely dissolved, add a mixed powder of 3.6 g of sodium carbonate and 0.9 g of sodium hydroxide, stir, add 0.5 g of the polyacrylonitrile / sodium-montmorillonite composite material obtained in step 2), heat to 70°C and maintain for 20 h to complete the amidoximation transformation of the polyacrylonitrile in the composite material, and obtain the sodium-montmorillonite-amidoximated polyacrylonitrile composite material of this comparative example.
[0079] The adsorption capacity of the sodium-montmorillonite-amidoxime-polyacrylonitrile composite material obtained in this comparative example was 62 mg / g after adsorption in 100 mL of uranyl solution containing uranium at a concentration of 8 ppm for 5 h.
[0080] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications made without departing from the spirit and principle of the present invention shall be equivalent replacement modes and shall be included in the protection scope of the present invention.
Claims
1. A small-particle allophane-amidoxime-treated polyacrylonitrile composite material for extracting uranium from seawater, characterized in that: The composite material is obtained by polymerizing allophane and acrylonitrile under the initiation of persulfate ions and undergoing amidoximation reaction, wherein the allophane is nanometer-scale.
2. The small-particle allophane-amidoxime-treated polyacrylonitrile composite material for extracting uranium from seawater according to claim 1, characterized in that: The particle size of the allophane is 3.5-5.0 nm, and the allophane is a nano hollow sphere structure with defect pores of 0.3-0.5 nm. Preferably, the allophane comes from an allophane suspension.
3. The small-size allophane-amidoxime-modified polyacrylonitrile composite material for extracting uranium from seawater according to claim 1 or 2, characterized in that: The polyacrylonitrile is prepared by polymerizing acrylonitrile monomer, and is compounded with allophane during the polymerization process, and finally undergoes amidoximation reaction using a hydroxylamine hydrochloride solution.
4. The small-particle allophane-amidoxime-treated polyacrylonitrile composite material for extracting uranium from seawater according to claim 1 or 2, characterized in that: The average particle size of the composite material is 26-35 nm, and the median cluster size is 480-560 nm.
5. The method for preparing the small-size allophane-amidoxime-treated polyacrylonitrile composite material for extracting uranium from seawater according to any one of claims 1 to 4, characterized in that: The following steps are involved: a) adding a persulfate ion solution to an allophane suspension, stirring and reacting to obtain a reaction solution; b) adding acrylonitrile monomer to the reaction solution obtained in step a) and heating and aging the mixture to form a polyacrylonitrile / alophane composite material; c) subjecting the composite material obtained in step b) to amidoximation reaction to obtain a small-particle-size allophane-amidoximated polyacrylonitrile composite material.
6. The preparation method according to claim 5, characterized in that The persulfate ions are from any one or more of potassium persulfate, ammonium persulfate or sodium persulfate, and the concentration of the persulfate ions is 1-10 g / L.
7. The preparation method according to claim 5, characterized in that: The amidoximation reaction occurs in a liquid medium, and the liquid medium is water or any one of dimethylformamide, dimethyl sulfoxide, cyclopentane, and ethyl nitrate.
8. The preparation method according to claim 5, characterized in that The concentration of the allophane suspension is 10-200 g / L.
9. The use of the small-particle allophane-amidoxime-treated polyacrylonitrile composite material for extracting uranium from seawater according to any one of claims 1 to 4, characterized in that: The uranyl ions are adsorbed at room temperature, and the concentration of the uranyl ions is 8-20 ppm.
10. The use according to claim 9, characterized in that The adsorption capacity is 320-480 mg / g for 2-5 hours at room temperature.
Citation Information
Patent Citations
Nanofiber material for extracting uranium from seawater and preparation method of nano-fiber material
CN107475798A
Nanoporous Seawater Uranium Extraction Adsorbent Materials and Preparation Methods for Pore Size Control
CN114984924B
Meso-porous silica particle supported amidoxime polymer uranium-absorbing material and preparation method thereof
CN109954484A
Method for preparing polyamidoxime / graphene nanobelt composite aerogel and method for separating and enriching uranium
CN111484644A
Nanometer composite pigment based on allophane and preparation method thereof
CN118703058A